Peran Mediasi Struktur Modal dalam Pengaruh Likuiditas dan Profitabilitas terhadap Nilai Perusahaan. Studi : Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia 2020-2022 - Juzi Najiha; Ikfani, Ikfani; Ahmad Miftahurridho Annizar; Benny Dhevyanto (CV. AFDIFAL MAJU BERKAH, 2024)
The importance of firm value represents a key rationale for investors to invest in a company. A firm with a high firm value provides a positive signal to potential investors, indicating a favorable investment environment. Factors such as profitability and liquidity can affect firm value. The principal aim of this research is to examine the relationship between firm value, profitability, and liquidity, with particular consideration given to the mediating effect of capital structure. This research employs a quantitative methodology and utilizes a total sample of 17 companies. The data analysis employed in this study makes use of SmartPLS 3.0 software. Based on the results of this study, firm value is not affected by profitability and liquidity because it shows p value > 0.05, specifically 0.344 and 0.073. Firm value is influenced by capital structure with p value 0.014, which in turn is influenced by profitability with p value 0.026. After the capital structure functions as a mediation, the p value shows a value of 0.046, which means that profitability affects the value of technology companies listed on the IDX for the 2020-2022 period. However, the relationship between liquidity and firm value shows a p value of 0.225 that means capital structure does not appear capable of mediating the relationship between liquidity and firm value.